Experimental research of the nuclear quasicontinuum and exploration of methods for the study of the nuclear continuum (2019)
Level lifetime and sidefeeding time measurements were performed on the excited states of the normally deformed bands of 83Y using the Doppler-Shift Attenuation Method (DSAM). The high spin states of 83Y were populated using the fusion-evaporation reaction 58Ni(32S,α3p)83Y at 135 MeV. 22 level lifetime and sidefeeding times were determined in most of the cases by comparing the lineshapes gated with transitions above and below the state under study. Quadrupole moments determined from lifetime measurements are in the range 1.1 − 3.1 eb, which are similar to the ones found for some of the neighboring nuclei. 83Y excited states were studied with paired Cranked Nilsson Strutinsky-Bogoliubov (CNSB) calculations. Unpaired Cranked Nilsson Strutinsky (CNS) calculations were used to specify configurations and study the band crossings. The measured |Qt | values show an agreement with CNSB calculations. Cranked shell model analysis evinced that the smallest quadrupole moment appears at the sharpest band crossing of the bands studied and CNSB calculations show an increase of the deformation thereinafter. The measured sidefeeding times were compared with predictions made by the simulations carried out with the Gammapace code. The results were in agreement with the experimental values by assuming reduced transition probabilities of the collective transitions in the continuum region, lying in the range 40 − 80 W.u. The combination of the Hk technique with the EOS (Energy Ordered Spectra) was studied as a possible new experimental technique to be used in future research of the nuclear continuum region. The experimental detector array PARIS was tested by Monte Carlo simulation for the application of the Hk technique. The results show that the simulated geometry for the PARIS array has a combined triggering effieciency at high energies which is very low for the implementation of the Hk technique, in spite that the design of the PARIS detectors was intended for the detection of high energy γ-rays. Adequate geometries and detector features of the experimental array for the application of the Hk-EOS technique are proposed.